The safety and efficacy of cannabinoids for the treatment of mental health and substance use disorders: protocol for a systematic review and meta-analysis - Jack Wilson; Andrew Langcake; Zachary Bryant; Tom P. Freeman; Janni Leung; Gary C. K. Chan; Amir Englund; Myfanwy Graham; Emily Stockings (Systematic Reviews)
Abstract There has been a global increase in the use of cannabinoids as a treatment for mental health (MH) and substance use disorders (SUD). In 2016, an Australian government-funded review found that although medicinal cannabinoids accounted for a small reduction in MH symptoms, the results varied according to study design. There has since been a rise in randomised controlled trials (RCTs) aiming to examine the efficacy of cannabinoids for the treatment of MH and SUD. Therefore, the current systematic review will (a) identify all RCTs examining the efficacy of cannabinoids in treating MH and SUD, (b) provide a quantitative or narrative synthesis of the evidence examining efficacy, and (c) synthesise adverse event data to examine evidence of harm. Electronic databases (Ovid MEDLINE, PsychINFO, Cochrane Central Register of Controlled Clinical Trials, Cochrane Database of Systematic Reviews, and Embase) were searched from 1980 to 24 May 2023. The study adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Guidelines. Articles will be screened to capture peer-reviewed RCTs evaluating the efficacy of plant-based and pharmaceutical cannabinoids in reducing or treating MH and SUD among people of any age. The Cochrane risk of bias tool 2.0 will be used to assess bias, while the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) tool will be used to assess the quality of evidence for each outcome. Study findings will be disseminated through published manuscripts, conferences, and health policy guidelines. Systematic review registration PROSPERO CRD42023392718.